Altered thermal preference by preoptic estrogen receptor alpha neurons in postpartum females - Nan Zhang; Meng Yu; Qianru Zhao; Bing Feng; Yue Deng; Jonathan C. Bean; Qingzhuo Liu; Benjamin P. Eappen; Yang He; Kristine M. Conde; Hailan Liu; Yongjie Yang; et al. (Molecular Metabolism)
Objective: This study aims to investigate how reproductive experience (RE) alters thermal preference and thermoregulation in female mice, with a focus on estrogen receptor alpha (ERα)-expressing neurons in the preoptic area (POA). Methods: Thermal preference and body temperature were measured in female mice with and without RE, and virgin female mice with selective deletion of ERα from the POA (ERαPOA-KO). The number and activity of ERα-expressing POA neurons (ERαPOA) were assessed using immunohistochemistry and in vitro electrophysiology in response to temperature changes and ERα agonist. Results: We showed that female mice prefer a cooler environment starting from late pregnancy and persisting long term postpartum. Female mice with RE (>4 weeks post-weaning) displayed lower body temperature and a lower thermal preferred temperature, and lost preference for warm environments (30 °C) but preserved avoidance of cold environments (15 °C). This was associated with a significant decrease in the number of ERαPOA neurons. Importantly, virgin female ERαPOA-KO mice displayed lower thermal preferred temperature and impaired warm preference, mimicking RE mice. We further found that distinct ERαPOA subpopulations can be regulated by temperature changes with or without presynaptic blockers, and by ERα agonist. More importantly, RE decreased the number of warm-activated ERαPOA neurons and reduced the excitatory effects of warmth and estrogen-ERα signaling, while cold-activated ERαPOA neurons were slightly enhanced in female mice with RE. Conclusion: Our results support that the thermosensing ability and estrogenic effects in ERαPOA neurons are regulated by reproductive experience, altering thermal preference.